Management of water resources in semi-arid: assessment of the drinking water supply in rural communities of Chapada do Apodi-RN (Sustainability in Debate, 2019)
Water is a natural resource, present in metabolic processes of living beings, which has been used for various purposes, especially human consumption. This study aimed to evaluate the system of supply and the quality of water for human consumption in rural communities of Chapada do Apodi, RN. The methodology consisted of identifying and evaluating the supply system as well as the quality of the water from the environmental perception and physical-chemical and biological analyses in water. Electrical conductivity, turbidity, dissolved oxygen, and Total Residue showed standards required for human consumption according to values ”‹”‹presented by current legislation. On the other hand, the results for pH parameters, total coliforms, and coliforms Escherichia coli type termotolerantes showed disagreement in accordance with the laws concerning the limits established for water bodies of water intended for human consumption. The infrastructural conditions of water supply systems, as well as the physical and chemical parameters of untreated water, were considered unsatisfactory.